An Exploratory Study of Organizational Alignment in U.S. Academic Libraries - Million, A.J.; Haggerty, Kenneth (Qualitative and Quantitative Methods in Libraries, 2020)
One way for academic libraries to increase funding from universities is by demonstrating the value they create through organizational alignment. This exploratory study tests if organizational alignment is effective. To test the argument that organizational alignment benefits university libraries, we studied athletic departments and library expenditures at Southeastern Conference universities in the United States. We examined mission statements and found that library missions aligned more directly with universities, but libraries saw less growth in their funding. This finding calls into question when, and where, organizational alignment is a practical strategy for library managers to pursue. Because our study was exploratory, we conclude future research should compare libraries with other academic units to test organizational alignment in additional contexts.